2005
DOI: 10.1007/s10826-005-5045-5
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Other Service Use by Youth in Therapeutic Foster Care and Group Homes

Abstract: Little is known about what additional services youth receive while they reside in out-of-home treatment settings. However, such information may be crucial for explaining effectiveness and variation in outcomes for youth in such settings. Our research examines patterns of multi-sector service use for youth in two settingsTherapeutic Foster Care and group homes. Data come from in-person interviews with Treatment Foster Parents and Group Home Staff for a NC state-wide sample of youth with psychiatric disorders an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 28 publications
4
34
0
Order By: Relevance
“…Although TFC is often considered as a substitute for group care, the population of youths served in TFC and group care show some differences on average. Studies that have descriptively compared TFC and group care have found that TFC youths are less disturbed (Berrick, Courtney & Barth, 1993), less likely to be taking psychotropic medications (Breland-Noble et al, 2004), and more likely to receive community-based supplementary services (Breland-Noble, Farmer, Dubs, Potter & Burns, 2005) than group care youth.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TFC is often considered as a substitute for group care, the population of youths served in TFC and group care show some differences on average. Studies that have descriptively compared TFC and group care have found that TFC youths are less disturbed (Berrick, Courtney & Barth, 1993), less likely to be taking psychotropic medications (Breland-Noble et al, 2004), and more likely to receive community-based supplementary services (Breland-Noble, Farmer, Dubs, Potter & Burns, 2005) than group care youth.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Although TFC is often considered as a substitute for group care, the population of youths served in TFC and group care show some differences on average. Studies that have descriptively compared TFC and group care have found that TFC youths are less disturbed (Berrick, Courtney & Barth, 1993), less likely to be taking psychotropic medications (Breland-Noble et al, 2004), and more likely to receive community-based supplementary services (Breland-Noble, Farmer, Dubs, Potter & Burns, 2005) than group care youth.However, it is not clear whether aggregate differences in youth populations served by TFC and group care are intentional or accidental. While policy and practice trends suggest that less troubled youth should be placed in less-restrictive settings, not enough evidence is available to anticipate which youth are best served in which environments.…”
mentioning
confidence: 99%
“…In general, youth served in treatment foster care were less disturbed (Berrick et al 1993), less likely to be treated with psychotropic medications (Breland-Noble et al 2004), and more likely to be receiving community-based services prior to placement (Breland-Noble et al 2005). Youth in treatment group care had greater behavioral and mental health disorders (Berrick et al 1993;Lee and Thompson 2008), and were likely to receive more restrictive services postdischarge than treatment foster care youth (Breland-Noble et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers (Beker 2001;Breland-Noble et al 2005;Frensch and Cameron 2002) note that many of the adolescents in TGH programs have failed in less restrictive programs which can possibly lead to a sense of failure and resistance to further treatment. Referral sources will many times state that these adolescents have been difficult to place due to their high level of maladaptive behaviors.…”
Section: Introductionmentioning
confidence: 99%